Relevansi Paradigma Thomas Kuhn terhadap Perkembangan Penelitian Modern - Dzaki Prayogo; Aulia Fahrunnisa; Amalia Najiha; Sean Rahayaan; Bina Prima Panggayuh (Yayasan Al-Afif, 2026)
This article examines the continuing relevance of Thomas Kuhn's paradigm theory for understanding how modern research develops, and offers a critical assessment of where the framework still holds and where it has been challenged. The problem addressed is whether Kuhn's concepts of normal science, anomaly, and paradigm shift still explain contemporary scientific practice across the natural sciences, social sciences, and Islamic studies. Using a qualitative library research method that synthesizes twenty primary and secondary sources published between 1959 and 2026 from Scopus-indexed journals and Google Scholar, the study traces Kuhn's core arguments and evaluates their application and critique in current scholarship. The results show that Kuhn's framework remains influential in explaining scientific communities and knowledge integration, including in Islamic education, although recent bibliometric and philosophical studies suggest that progress is often more cumulative than revolutionary and that incommensurability has been substantially revised. The article argues that Kuhn's paradigm remains a valuable, though contested, analytical lens, and it proposes that Islamic Religious Education research adopt a post-normal, integrative reading of Kuhn rather than a literal revolutionary one.